Answer:
C. vertical compression
Explanation:
![\left\begin{array}{ccc}f(-2)=8\\g(-2)=4\end{array}\right\}\Rightarrow g(x)=(1)/(2)f(x)\\\\\left\begin{array}{ccc}f(-1)=6\\g(-1)=3\end{array}\right\}\Rightarrow g(x)=(1)/(2)f(x)\\\left\begin{array}{ccc}f(0)=8\\g(0)=4\end{array}\right\}\Rightarrow g(x)=(1)/(2)f(x)\\\left\begin{array}{ccc}f(1)=14\\g(1)=7\end{array}\right\}\Rightarrow g(x)=(1)/(2)f(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/zqag2invticyvz0opf6fnh4ma2ei6w9bxg.png)
![\large\boxed{g(x)=(1)/(2)f(x)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/v04x34pzshubuex8tz5s6q18napllm5a0p.png)
f(x - b) - shifted b units to the right
f(x + b) - shifted b units to the left
f(x) + b - shifted b units up
f(x) - b - shifted b units down
f(-x) - reflected across the y -axis
-f(x) - reflected across the x -axis
f(nx) - a horizontal compression by a factor of n
f(x/n) -a horizontal stretch by a factor of n
nf(x) - a vertical stretch by a factor of n
f(x)/n - a vertical compression by a factor of n